2018
DOI: 10.1523/jneurosci.0272-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Modality-Independent Coding of Scene Categories in Prefrontal Cortex

Abstract: Natural environments convey information through multiple sensory modalities, all of which contribute to people's percepts. Although it has been shown that visual or auditory content of scene categories can be decoded from brain activity, it remains unclear how humans represent scene information beyond a specific sensory modality domain. To address this question, we investigated how categories of scene images and sounds are represented in several brain regions. A group of healthy human subjects (both sexes) par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 51 publications
6
27
0
Order By: Relevance
“…Further analysis of these results indicated that not only were the multivariate patterns produced by tastes and pictures completely unrelated, but the decoding models relied most heavily on independent sets of voxels when classifying food pictures or tastes. These results are partly in keeping with previous studies which have generated similar null results when attempting cross-modal classification within primary sensory cortices (24,25).…”
Section: Crossmodal Decodingsupporting
confidence: 91%
See 1 more Smart Citation
“…Further analysis of these results indicated that not only were the multivariate patterns produced by tastes and pictures completely unrelated, but the decoding models relied most heavily on independent sets of voxels when classifying food pictures or tastes. These results are partly in keeping with previous studies which have generated similar null results when attempting cross-modal classification within primary sensory cortices (24,25).…”
Section: Crossmodal Decodingsupporting
confidence: 91%
“…These results demonstrate how higher-order inferences derived from stimuli in one modality (in this case vision) can be represented in brain regions typically thought to represent only low-level information about a different modality (in this case taste). Broadly, these results echo previous neuroimaging findings on multisensory processing within vision and audition, which demonstrate that early sensory cortical areas are able to represent the inferred sensory properties of stimuli presented via another sensory channel (24,25). Taken together, these findings are consistent with claims that both higher-order and presumptively unimodal areas of neocortex are fundamentally multisensory in nature (26).…”
Section: Multivariate Patterns Representing Tastes and Food Picturessupporting
confidence: 88%
“…Evaluation of sounds together with contextual information also falls within the purview of the PFC. In an fMRI study which showed the context-dependent nature of sound processing, [26] used 640 images from four scene categories (beach, office, city, forest) and 64 sound clips that corresponded to the same scenes (e.g., sound of waves on beach, people talking in the office) to discover that, when the two modalities are congruent to the same scene category, a similar neural activation pattern in response to visual and auditory stimuli occurs only in the PFC, suggesting its critical role in coordinating abstract visual and auditory scenes relative to context. Neural activation patterns were found to be distinct in different categories of scenes, indicating that contextual interpretations of scenes may fall within the purview of the PFC.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that various components of scenes are processed across several brain regions of the sceneselective network in the visual cortex, such as the parahippocampal place area (PPA, Epstein & Kanwisher, 1998), the retrosplenial cortex (RSC, Maguire, 2001), and the occipital place area (OPA, Dilks et al, 2013). However, recent studies have shown that visual scene processing takes place beyond the visual cortex and involves the associative cortex such as the parietal (Silson et al, 2016;Silson et al, 2019) and the prefrontal cortex (Jung et al, 2018). Does this indicate that the scene processing network can be extended to the prefrontal cortex (PFC)?…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that scene images and sounds elicit neural representations of scene categories in PFC. Intriguingly, these representations are modality-independent, suggesting that PFC represents scene content in an abstract way (Jung et al, 2018). Natural scenes also comprise other attributes, often referred to as global scene properties, such as openness, temperature, or transience (Greene & Oliva, 2009), which are also processed in scene-selective visual brain regions (Kravitz et al, 2011;Park et al, 2011;Persichetti and Dilks, 2019).…”
Section: Introductionmentioning
confidence: 99%